North American Rendering: processing high quality protein and fats for feed - Meeker,David L. (2009)
One third to one half of each animal produced for meat, milk, eggs, and fiber is not consumed by humans. These raw materials are subjected to rendering processes resulting in many useful products. Meat and bone meal, meat meal, poultry meal, hydrolyzed feather meal, blood meal, fish meal, and animal fats are the primary products resulting from the rendering process. The most important and valuable use for these animal by-products is as feed ingredients for livestock, poultry, aquaculture, and companion animals. There are volumes of scientific references validating the nutritional qualities of these products, and there are no scientific reasons for altering the practice of feeding rendered products to animals. Government agencies regulate the processing of food and feed, and the rendering industry is scrutinized often. In addition, industry programs include good manufacturing practices, HACCP, Codes of Practice, and third-party certification. The rendering industry clearly understands its role in the safe and nutritious production of animal feed ingredients and has done it very effectively for over 100 years. The availability of rendered products for animal feeds in the future depends on regulation and the market. Regulatory agencies will determine whether certain raw materials can be used for animal feed. The National Renderers Association (NRA) supports the use of science as the basis for regulation while aesthetics, product specifications, and quality differences should be left to the market place. Without the rendering industry, the accumulation of unprocessed animal by-products would impede the meat industries and pose a serious potential hazard to animal and human health.